THE EARLY CHILDHOOD EDUCATION IN THE CITY OF MARILIA (SP): THE OFFER, AND THE INFRASTRUCTURE AND THE NATIONAL EDUCATION PLAN - Brandao, Carlos da Fonseca [UNESP]; Lopes, Silvana Fernandes [UNESP]; Rodrigues Alves, Catharina Edna [UNESP]; Jeremias Urel, Ana Laura [UNESP] (Unesp-faculdade Ciencias & Letras, 2016)
This article presents the results of a research carried out along with the Municipal Secretary of education in the city of Marilia (SP), which sought to diagnose the situation of municipal Elementary Schools (EMEI) in Marilia regarding to issues of supply, service and infrastructure, having as main parameter the National Education Plan (PNE) which ran until 2011 (law no 10.17201). Faced with the found situation, this article also analyzes the same issues, of the current National Education Plan (PNE-law no 13.00514), in order to check how far we are (or not) of achieving goal no. 1 of the current PNE, on early childhood education.
Keywords: National Education Plan; Early Childhood Education; Offer, service and infrastructure